2009
DOI: 10.1124/jpet.109.157388
|View full text |Cite
|
Sign up to set email alerts
|

WS-50030 [7-{4-[3-(1H-inden-3-yl)propyl]piperazin-1-yl}-1,3-benzoxazol-2(3H)-one]: A Novel Dopamine D2 Receptor Partial Agonist/Serotonin Reuptake Inhibitor with Preclinical Antipsychotic-Like and Antidepressant-Like Activity

Abstract: The preclinical characterization of propyl]piperazin-1-yl}-1,3-benzoxazol-2(3H)-one] is described. In vitro binding and functional studies revealed highest affinity to the D 2 receptor (D 2L K i , 4.0 nM) and serotonin transporter (K i , 7.1 nM), potent D 2 partial agonist activity (EC 50 , 0.38 nM; E max , 30%), and complete block of the serotonin transporter (IC 50 , 56.4 nM). Consistent with this in vitro profile, WS-50030 (10 mg/kg/day, 21 days) significantly increased extracellular 5-HT in the rat medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Nonetheless, the therapeutic benefits of these drugs appear promising, indicating that these types of antipsychotics may warrant additional attention. For example, preclinical studies have shown that the putative antipsychotic WS500‐30, a partial D2 receptor agonist and serotonin transporter blocker, may have potential for the therapeutic management of both psychosis and cognitive defects in schizophrenia [56]. Similarly, the mGlu2/3 receptor glutamate agonist LY404039, also with partial activity at the D2 receptor [57–59], is efficacious in alleviating both the positive and negative symptoms [60].…”
Section: Dopamine Receptor Homomersmentioning
confidence: 99%
“…Nonetheless, the therapeutic benefits of these drugs appear promising, indicating that these types of antipsychotics may warrant additional attention. For example, preclinical studies have shown that the putative antipsychotic WS500‐30, a partial D2 receptor agonist and serotonin transporter blocker, may have potential for the therapeutic management of both psychosis and cognitive defects in schizophrenia [56]. Similarly, the mGlu2/3 receptor glutamate agonist LY404039, also with partial activity at the D2 receptor [57–59], is efficacious in alleviating both the positive and negative symptoms [60].…”
Section: Dopamine Receptor Homomersmentioning
confidence: 99%
“…Brennan et al, 2010) and in other cell systems. For example, we have validated cAMP accumulation in CHO cells transfected with the serotonergic 5-HT 1A and cannabinoid CB 1 and CB 2 receptors (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Aripiprazole (0.1 --1 mg/kg i.p.) caused a dose-dependent antagonism of psychostimulant-induced stereotypies (sniffing--licking--gnawing syndrome) and climbing behavior in CF-1 mice [88]. Aripiprazole has also been shown to dosedependently reverse psychostimulant-induced disruption of PPI in rats (1, 3, 10 and 30 mg/kg p.o.)…”
Section: Nps-related Behavioral Changes 411 Psychostimulant-inducedmentioning
confidence: 97%
“…Much preclinical work has focused on the presumed reduced side effects of aripiprazole versus second-generation antipsychotics [81][82][83][84][85][86][87][88][89][90]. Though aripiprazole has not been evaluated in established animal models for AD, several preclinical studies underpin the presumed efficacy of aripiprazole with regard to NPS-related behavioral changes, as well as cognitive deficits in laboratory animals.…”
Section: Preclinical Workmentioning
confidence: 98%
See 1 more Smart Citation